2016
DOI: 10.46364/njmlm.v4i1.292
|View full text |Cite
|
Sign up to set email alerts
|

A case study of Readers Theatre in a primary Norwegian EFL class

Abstract: This article presents research on a case study of the use of Readers Theatre (RT), a group reading aloud activity in which a text is divided into small segments, in a sixth grade English as a Foreign Language (EFL) class in Norway. A mixed ability class of 27 readers, divided into groups of five to six pupils, rehearsed and performed fairy tales adapted for RT. The aims were to find out how the teachers and pupils experienced RT and how it influenced the development of the pupils’ reading, motivation and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Supporting Myrset (2014) and Myrset and Drew (2016), the study showed that the learners' fluency improved and that they made considerably fewer pronunciation and word recognition mistakes in the performances compared to the rehearsals. They had become conscious of the need to be as accurate as possible and through peer and especially teacher assistance, had improved their reading accuracy and fluency.…”
Section: Readers Theatrementioning
confidence: 82%
See 4 more Smart Citations
“…Supporting Myrset (2014) and Myrset and Drew (2016), the study showed that the learners' fluency improved and that they made considerably fewer pronunciation and word recognition mistakes in the performances compared to the rehearsals. They had become conscious of the need to be as accurate as possible and through peer and especially teacher assistance, had improved their reading accuracy and fluency.…”
Section: Readers Theatrementioning
confidence: 82%
“…Video recordings enabled the researcher to compare pronunciation, word recognition and fluency during the first rehearsals and performances of the groups, something which was original in the research on RT in an L2 context. Substantial gains were recorded in pronunciation, word recognition and fluency, especially amongst the struggling learners in the class (Myrset, 2014;Myrset & Drew, 2016). In addition to improvement in their reading skills, the learners produced a good deal of text in their Christmas stories, were enthusiastic and engaged in the project, became more confident about their reading, and were eager to participate in another RT project.…”
Section: Readers Theatrementioning
confidence: 97%
See 3 more Smart Citations